2015
DOI: 10.1016/j.neuroscience.2015.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Increased cross-education of muscle strength and reduced corticospinal inhibition following eccentric strength training

Abstract: The results show that eccentric training uniquely modulates corticospinal excitability and inhibition of the untrained limb to a greater extent than concentric training. These findings suggest that unilateral eccentric contractions provide a greater stimulus in cross-education paradigms and should be an integral part of the rehabilitative process following unilateral injury to maximize the response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 43 publications
8
95
0
Order By: Relevance
“…31 Using a transcranial magnetic stimulation method, unilateral training protocols were shown to reduce intracortical inhibition and silent period duration as well as increase corticospinal excitability. 32,33 The physiologic bases for these changes are not understood, but our data support the view that there is bidirectional communication between the central brain areas and yoked and agonist-antagonist muscle pairs. As indicated, it is important to remember that resistance exercise resulted in increased muscle expression of IGF-1.…”
Section: Discussionsupporting
confidence: 63%
“…31 Using a transcranial magnetic stimulation method, unilateral training protocols were shown to reduce intracortical inhibition and silent period duration as well as increase corticospinal excitability. 32,33 The physiologic bases for these changes are not understood, but our data support the view that there is bidirectional communication between the central brain areas and yoked and agonist-antagonist muscle pairs. As indicated, it is important to remember that resistance exercise resulted in increased muscle expression of IGF-1.…”
Section: Discussionsupporting
confidence: 63%
“…It is well documented that resistance training of one limb increases muscle strength of the other limb, which is known as the cross‐educational effect . A similar phenomenon is observed for eccentric exercise‐induced muscle damage such that the initial bout of eccentric exercise of one limb attenuated the magnitude of muscle damage of the contralateral homologous muscle .…”
Section: Introductionmentioning
confidence: 72%
“…The possible mechanisms of the protection conferred by 2MVIC on 30MVEC of the contralateral arm have not been explored, but some speculations could be made. It is well documented that resistance training of one limb increases muscle strength of the homologous muscle of the opposite limb, which is known as the cross‐education effect . Diffusion of impulses between hemispheres, co‐activation via bilateral corticospinal pathways, learning in coordination, and afferent modulation have been described as potential candidates for the cross‐education effect .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While conventional exercise is not considered to be an approach to motor priming, in non-disabled individuals, some studies have concluded that resistance training is associated with increased CSE (26, 31), and with greater twitch forces of the cortically evoked motor response (32). This may suggest that changes in CSE are similar for skill training and strength training (26).…”
Section: Introductionmentioning
confidence: 99%